A Study of Genotyping for Management of Human Papillomavirus-Positive, Cytology-Negative Cervical Screening Results - Schiffman, M. (J Clin Microbiol, 2014)
The effective management of women with human papillomavirus (HPV)-positive, cytology-negative results is critical to the introduction of HPV testing into cervical screening. HPV typing has been recommended for colposcopy triage, but it is not clear which combinations of high-risk HPV types provide clinically useful information. This study included 18,810 women with Hybrid Capture 2 (HC2)-positive, cytology-negative results and who were age ≥30 years from Kaiser Permanente Northern California. The median follow-up was 475 days (interquartile range [IQR], 0 to 1,077 days; maximum, 2,217 days). The baseline specimens from 482 cases of cervical intraepithelial neoplasia grade 3 or cancer (CIN3+) and 3,517 random HC2-positive noncases were genotyped using 2 PCR-based methods. Using the case-control sampling fractions, the 3-year cumulative risks of CIN3+ were calculated for each individual high-risk HPV type. The 3-year cumulative risk of CIN3+ among all women with HC2-positive, cytology-negative results was 4.6%. HPV16 status conferred the greatest type-specific risk stratification; women with HC2-positive/HPV16-positive results had a 10.6% risk of CIN3+, while women with HC-2 positive/HPV16-negative results had a much lower risk of 2.4%. The next most informative HPV types and their risks in HPV-positive women were HPV33 (5.9%) and HPV18 (5.9%). With regard to the etiologic fraction, 20 of 71 cases of cervical adenocarcinoma in situ (AIS) and adenocarcinoma in the cohort were positive for HPV18. HPV16 genotyping provides risk stratification useful for guiding clinical management; the risk among HPV16-positive women clearly exceeds the U.S. consensus risk threshold for immediate colposcopy referral. HPV18 is of particular interest because of its association with difficult-to-detect glandular lesions. There is a less clear clinical value of distinguishing the other high-risk HPV types.